Rodents as possible reservoirs of leptospirosis in extensive swine breeding systems - Cvetnič, Željko; Margaletić, Josip; Đikić, Marija; Glavaš, Milan; Ðjikić, Domagoj; Špicić, Silvio; Jurić, Ivan; Salajpal, Krešimir (Acta Agraria Kaposváriensis, 2002)
In the territory of the Forestry of Velika Gorica in the economic unit „Turopoljski Lug” investigations were carried out on the distribution of leptospira in rodents and swine of autochthonous breed of Turopolje living on that area and traditionally being extensively bred. In total the samples of 31 rodents of the following species were analysed: Apodemus (A.) agrarius, A. sylvaticus, A. flavicollis Clethrionomys glareolus, Microtus (M.) agrestis and M. arvalis. In addition, 52 blood sera of Turopolje swine were analysed. The distribution of leptospirosis in rodents and swine was demonstiated by isolation of rhinoculture (rodents) and findings of antibodies to leptospira by the reaction of microscopic agglutination. The antibodies to leptospirosis were established in six (19.4%) out of 31 blood samples of rodents analysed and of all the samples bacteriologically analysed leptospira were isolated from 1 sample 3.2%. The largest number of positive serological reactions was established in the species A. flavicollis and the antibodies to leptospira serovar (sv.) sv. australis (in three cases) and sv. pomona (in one case) were demonstrated. In the species C. graleoulos sv. sejroe and sv. australis (in one case each) were established. In swine the antibodies were established in eleven (21.1%) blood samples out of 52 blood samples of Turopolje swine analysed. The antibodies to sv. ieterohaemorhagiae (two swine), sv. australis (seven swine), sv. pomona and sv. grippotyphosa (two swine) were demonstrated. Our investigation revealed the distribution of identical sv. of leptospira in rodents and swine living in the same territory (sv. australis and sv. pomona). The mice-like rodents are natural reservoirs of leptospira, thus representing a significant potential source of infection for swine kept in extensive breeding systems.